STAGES OF DEVELOPMENT OF THE AFU STRATEGIC COMMUNICATIONS LEGAL SUPPORT - Ostapenko, I. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The paper provides a scientific and legal analysis of the development stages of the legal support of the Armed Forces of Ukraine (AFU) strategic communications, as well as the analysis of the existing legislation, regulations and bylaws in the field. The research also focuses on the notion of strategic communication in the national legislation of Ukraine. The findings allow to stipulate that the development of the legal support of the AFU strategic communications is heavily influenced by globalization, rise of the digital technologies, widespread usage of social media, increased virtualization due to COVID-19 pandemic, rapid dissemination of information and an increased level of information-related threats as part of hybrid aggression. The development of the legal support of the Armed Forces of Ukraine (AFU) strategic communications is divided into the following stages: first stage, 2010-2014 – laying the foundations for the strategic communications; second stage, 2014-2015 – developing the strategic communications framework; third stage, 2016 – until now – institutionalizing the strategic communications in the Armed Forces of Ukraine. Characteristics of all stages have been identified. The paper establishes a systematic framework for the existing legislation that regulates the use of the strategic communications capabilities in the Armed Forces of Ukraine. Research findings substantiate the need for further studies in the field of the legal support of the AFU strategic communications. The research also highlights the need to improve the state and defense governance in the field of communications, amend the existing legislation to correct and restate the terms and definitions related to strategic communications and to adopt new legislation in accordance with the principles, standards and best practices of NATO and EU member-states.